Advantages and Complications of Fisch Partial Mastoidotympanectomy for Tumors of the Retromandibular Fossa and Poststyloid Space - Catalano, Dominic J.; Gluth, Michael B. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective This study aims to characterize a single surgeon's experience with resection of tumors of the retromandibular fossa and poststyloid space utilizing the Fisch partial mastoidotympanectomy (FPMT) technique of partial temporal bone resection.Design Retrospective review.Setting Academic medical center.Participants Seven patients who underwent tumor resection with FPMT.Main Outcome Measures Complications.Results Six males and one female underwent FPMT, with ages ranging from 44 to 79 years. The facial nerve was sacrificed in six cases, no cases were converted to more extensive temporal bone resection procedures, and no postoperative hearing loss occurred. The only intraoperative complication experienced was a violation of the external auditory canal in four cases, which resulted in postoperative wound healing issues in two cases.Conclusions FPMT allows for the release of tumors of the poststyloid space and retromandibular fossa without compromise of hearing status. Preservation of external auditory canal soft tissues is challenging, and the violation is experienced relatively frequently due to shearing forces during soft tissue retraction. When encountered, robust repair of defects is encouraged to prevent further wound healing complications.
Keywords: temporal bone resection; parotid gland malignancy; temporal bone tumor; mastoidectomy